THE MEANING OF LUQMANUL HAKIM'S WILL IN SURAH LUQMAN VERSES 13-19 - Hanif Maulana (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research examines the meaning of Luqmanul Hakim's will in SurahLuqman verses 13-19. The research method used in this research is a qualitative method with a content analysis approach. The data collection technique used by the author in this article is to translate verses from the Al-Qur'an, interpret andconclude the understanding that researchers have sought from these verses, so as to obtain results that are more detailed and clear and can be understood easily by everyone. reader. There are several values of Islamic educationcontained in the Al-Qur'an Surah Luqman verses 13-19, basically covering three fundamental education, namely; aqidah education, moral education, and sharia education. The aqidah education contained in Luqman's letter is in verse 13, namely "O my son, do not associate partners with Allah, indeed to associatepartners with (Allah) is truly great injustice." Then the moral education stated in Luqman's letter is in verses 14, 15, 16, 18 and 19, in verses 14 and 15 it explains the command to do good to both parents, in verse 16 it states about retribution for bad deeds, even if it is a mustard seed, Allah will still avengethem, in verse 18 it states that you should not be arrogant towards fellow humans, and in verse 19 it explains human behavior or movements, and recommends being gentle and humble. Then the education stated in Luqman'sletter is in verse 17, namely "O my son, establish prayer and order (humans) todo good and prevent (them) from doing evil and be patient with what befalls you."